Economic benefits of sustainable, forage-based cattle systems in Colombia and Nicaragua - Burkart, Stefan; Enciso, Karen; Díaz, Manuel Francisco; van der Hoek, Rein (International Grassland Congress 2023, 2023)
Forage-based cattle systems play a key role in rural economies of developing countries in terms of food security and poverty alleviation, particularly in tropical Latin America. However, they are often related to being a major cause of negative environmental impacts by contributing to increased greenhouse gas emissions, land degradation, and the reduction of biodiversity. Significant resources have been allocated to research and development in forage material improvement, including selection and breeding. A broad range of improved materials were released by private and public sector actors showing superior characteristics in terms of productivity and environmental impacts compared to native or naturalized materials. Profitability is a fundamental attribute to incentivize or generate adoption of new systems by cattle producers, but this information is often not available to the livestock producer or the extension agents supporting decision-making processes. This research provides an overview on the economic viability of integrating different improved forage varieties in sustainably intensified cattle production systems in Colombia and Nicaragua. Our evaluations show that, despite higher establishment and management costs, integrating improved forage technologies (and management practices) in sustainably intensified cattle systems, either as monoculture, grass-legume associations, silvo-pastoral systems, or in combination with improved management strategies (e.g., intensive, or rotational grazing), not only make sense from the environmental and productive perspectives but also in terms of economic viability. In nearly all evaluated scenarios, the economic indicators improve by integrating improved forage technologies. Strong increases were observed for the following indicators: a) net income, b) unit profit margin, c) Net Present Value, d) Internal Rate of Return, and f) benefit-cost ratio. Strong decreases were observed for the following indicators: a) unit production cost, b) risk of obtaining economic loss, c) payback time, d) minimum area required for a profitable system, and e) sensitivity of the system to external shocks. This information will help cattle producers, extensionists and policymakers to make more holistic and informed land-use decisions that include productive, environmental, economic, and social benefits, and by this contributes to the broader adoption of more sustainable production systems.